Business registration and firm performance: a case of maize traders in Malawi. Issue 7 (2nd October 2020) - Kankwamba, Henry; Kornher, Lukas
ABSTRACT: Small businesses could spur economic growth. Most African small businesses are not formally registered, and informality leads to loss of government revenue. This article assesses the effect of business registration on firm performance in Malawi's maize sub-sector. The study uses panel data of 172 traders from Malawi, and instrumental variable estimation on a systematically drawn sample. The results indicate that when registered, traders make four times less profits. Variables such as sex, exporters, information gathering and general trading had positive effects on business profitability. Unless the business environment is reformed in favour of small businesses it does not pay to register.